STANDAR OPERASI KOLABORATIF: PENGEMBANGAN MODEL KEBIJAKAN ADAPTIF DINAMIS - Nani, Yacob; Zuchri Abdussamad; Jurico Abdussamad; Rustam Tohopi (Program Studi Administrasi Negara Universitas Serang Raya, 2024)
Adaptive management Governance and Dynamic institutional systems are being promoted as recipes for improving policy performance. In our opinion, there is relevance to this basic assumption with research findings showing that the empowerment model in implementing public service policies will be effective if it is carried out with adaptive policy governance and a dynamic bureaucracy. This argument is supported by empirical facts that there is a coherent relationship between adaptive governance and dynamic bureaucratic systems in moderating increased public participation and support for policy implementation. So the purpose of this study is to identify the factors that lead to the success of public policy. Through in-depth qualitative analysis. the implications of the research results are developed as a Dynamic-Adaptive policy model with the conclusion that adaptive policy governance does not work effectively without the support of a dynamic institutional system.